Bandwidth Capacity Analysis on Fiber Optic Networks for E - learning at Pakuan University - Evyta Wismiana; Anang Suryana; Waryani Waryani; Adam Muhamad Ali; ChairinaufalÂ SalasaÂ Usmi (Universitas Nusa Putra, 2023)
Pakuan University (UNPAK) currently has 6 faculties for undergraduate programs, vocational schools, graduate, and post-graduate programs, with an interconnected fiber optic network. The management of the fiber optic network is carried out by Putik as O & M in collaboration with Moratel as the internet connection provider with a bandwidth of 550 Mbps. Analyzing the bandwidth capacity of the fiber optic network is crucial for the implementation of e-learning at Pakuan University. E-learning plays an important role in supporting the teaching and learning process during the Covid-19 pandemic, whether online or remote learning. Based on the daily user recapitulation, it is known that e-learning usage peaks between 08.50 – 10.30 Western Indonesian Time on an usual Monday with 6,505 users in total. The Faculty of Social and Cultural Sciences (FISIB) holds the highest usage of 143.23 Mbps, along with other faculties which exceeds the predetermined capacity of 40 Mbps each. This caused the Simple Queue method to experience access delays of even Request Time Out (RTO) conditions. Therefore, the Simple Queue method is no longer adequate, making the Queue Tree method the better option.